Inhibition of NMDA Receptors Prevents the Loss of BDNF Function Induced by Amyloid β - Tanqueiro, Sara R.; Ramalho, Rita M.; Rodrigues, Tiago M.; Lopes, Luísa V.; Sebastião, Ana M.; Diógenes, Maria J. (Frontiers in Pharmacology, 2018)
Brain-derived neurotrophic factor (BDNF) plays important functions in cell survival and differentiation, neuronal outgrowth and plasticity. In Alzheimer’s disease (AD), BDNF signaling is known to be impaired, partially because amyloid β (Aβ) induces truncation of BDNF main receptor, TrkB-full length (TrkB-FL). We have previously shown that such truncation is mediated by calpains, results in the formation of an intracellular domain (ICD) fragment and causes BDNF loss of function. Since calpains are Ca2+-dependent proteases, we hypothesized that excessive intracellular Ca2+ build-up could be due to dysfunctional N-methyl-d-aspartate receptors (NMDARs) activation. To experimentally address this hypothesis, we investigated whether TrkB-FL truncation by calpains and consequent BDNF loss of function could be prevented by NMDAR blockade. We herein demonstrate that a NMDAR antagonist, memantine, prevented excessive calpain activation and TrkB-FL truncation induced by Aβ25-35. When calpains were inhibited by calpastatin, BDNF was able to increase the dendritic spine density of neurons exposed to Aβ25-35. Moreover, NMDAR inhibition by memantine also prevented Aβ-driven deleterious impact of BDNF loss of function on structural (spine density) and functional outcomes (synaptic potentiation). Collectively, these findings support NMDAR/Ca2+/calpains mechanistic involvement in Aβ-triggered BDNF signaling disruption.